(untitled) (Vietnam Journal of Community Medicine, 2022)
Extramedullary Hematopoiesis (EMH) is the expansion of stem cells, hematopoietic progenitor cells and their differentiation outside the bone marrow. This condition occurs as a compensatory mechanism for the ineffective hematopoiesis of the bone marrow. Pathological EMH is triggered by hematopoietic disorders and other pathological stress conditions, such as infections, malignant tumor, anemia, and metabolic disorders. Pathological EMH has been reported to occur in many organs, and sites of pathological EMH may be involved in reactivation of embryonic hematopoietic structures in these organs. Pathological EMH has been extensively studied in recent years. In particular, pathological EMH caused by end-stage malignancy contributes to tumor immunosuppression. Thus, a deeper understanding of the mechanism of pathological EMH could be beneficial for the development of therapies against tumor development processes. We report a rare case of an extramedullary hematopoietic tumor in the mediastinum, diagnosed by histopathology, for reference to colleagues.